Witnesses with Mental Disabilities: Accommodations and the Search for Truth - Neta Ziv (Disability Studies Quarterly, 2007)
In 2005 Israel enacted a comprehensive law requiring accommodations for persons with disabilities in the justice system. The Investigation and Testimony Procedural Act (Accommodations for Persons with Mental or Cognitive Disabilities) of 2005 applies to police investigations and court testimony of persons with mental and cognitive disabilities, if they are suspected of committing a severe crime, witness such a crime, or are victims of one. Many of the accommodations required by the law involve input from professionals in therapeutic disciplines such as psychiatrists, psychologists, criminologists and social workers. Thus, therapeutic professionals offer the judiciary alternative measures to understand and construe human behavior. Their intervention in the legal field occurs in what seems to be the most fundamental function of courts, through which they base their legitimacy and their claim to exclusive knowledge and skill - the ability to ascertain the truth. This paper probes the encounter between the justice system and these disciplines at the evidentiary stage, when persons with mental and cognitive disabilities testify in court about crimes committed against them. Persons with mental disabilities are more likely than others to become victims of crime and assault. Only lately has the justice system begun to address measures that must be undertaken to protect them from abuse; the Israeli Act is a favorable step in this direction.